Methods of Comparing ECG Reconstruction - Prauzek, M.; Penhaker, M. (2009 2nd International Conference on Biomedical Engineering and Informatics, 2009)
The paper describes methods of comparing calculated ECG signal with real signal. Five examination methods of ECG-signal reconstruction from reduced system were proposed in this description. These methods prove reconstruction and evaluate results. They are based on statistic methods, nonparametric approaches and autoregressive models.